2014
DOI: 10.2147/ott.s63168
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab plus chemotherapy versus chemotherapy alone in advanced non-small-cell lung cancer: a multicenter, randomized, open-label Phase II study

Abstract: BackgroundThe purpose of this study was to evaluate the safety and efficacy of nimotuzumab in combination with chemotherapy (docetaxel and carboplatin) versus chemotherapy alone in patients with stage IIIB/IV non-small-cell lung cancer.MethodsThis multicenter, open-label, Phase II study randomized 110 patients to receive nimotuzumab plus chemotherapy (nimotuzumab group) or chemotherapy alone (control group), and comprised concomitant, maintenance, and follow-up phases. Nimotuzumab 200 mg was administered once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…Other common adverse events were fatigue and gastrointestinal reaction. Nimotuzumab‐related skin draught and pruritus, which were reported previously in other studies, were not noticed in the present study . Interestingly, unlike for other EGFR inhibitors, an acne‐like rash was not observed.…”
Section: Discussionsupporting
confidence: 69%
“…Other common adverse events were fatigue and gastrointestinal reaction. Nimotuzumab‐related skin draught and pruritus, which were reported previously in other studies, were not noticed in the present study . Interestingly, unlike for other EGFR inhibitors, an acne‐like rash was not observed.…”
Section: Discussionsupporting
confidence: 69%
“…This has led to a further phase III randomized study to evaluate the efficacy of the combination of nimotuzumab with other chemotherapy drugs as a first line treatment for stage IIIB-IV NSCLC (24). A431 cells, a vulvar epidermoid carcinoma cell line with high EGFR expression demonstrated less receptor activation upon ligand binding when treated with nimotuzumab (25).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the ORR was 50% and median PFS was 6.7 months. Similarly, a previous phase II study reported an ORR of 54% in a group of NSCLC patients administered nimotuzumab plus chemotherapy …”
Section: Discussionmentioning
confidence: 62%
“…Nimotuzumab is well tolerated up to 400 mg per week . In previous clinical trials, nimotuzumab was administered in weekly doses of 200 mg or 400 mg . Considering the half life of nimotuzumab, safety, and the need for fewer infusions, nimotuzumab was administered at a dose of 400 mg on days 1 and 8 for 21 days in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation